Alterations in blood microbiota after colonic cancer surgery. Issue 6 (6th October 2020) - Søby, J H; Watt, S K; Vogelsang, R P; Servant, F; Lelouvier, B; Raskov, H; Knop, F K; Gögenur, I
Abstract: Background: Mechanisms contributing to the perioperative stress response remain poorly understood. This study investigated changes in the amount of bacterial DNA in blood and the diversity of blood microbiota in the perioperative period in patients undergoing minimally invasive surgery for colonic cancer in an enhanced recovery after surgery setting. Methods: DNA encoding the bacterial 16S ribosomal RNA gene (16S rDNA) in whole blood obtained the day before surgery, and on postoperative day (POD) 1 and POD 10–14 was amplified and quantified by PCR before sequencing for taxonomic assignment. Richness, evenness and similarity measures were calculated to compare microbiota between days. Differences in relative abundance were analysed using the linear discriminant analysis effect size (LEfSe) algorithm. Results: Thirty patients were included between January and July 2016. The concentration of bacterial 16S rDNA in blood increased between the day before surgery and POD 1 ( P = 0.025). Bacterial richness was lower on POD 10–14 than on the day before surgery and POD 1 (both P < 0·001). LEfSe analysis comparing the day before surgery and POD 10–14 identified changes in the abundance of several bacteria, including Fusobacterium nucleatum, which was relatively enriched on POD 10–14. Conclusion: These findings suggest that the blood of patients with colonic cancer harbours bacterial 16S rDNA, which increases in concentration after surgery. Graphical Abstract: This study investigated changes in the amount of bacterial DNA in blood and the diversity of blood microbiota in the perioperative period in 30 patients undergoing minimally invasive surgery for colonic cancer. DNA encoding the bacterial 16S ribosomal RNA gene (16S rDNA) was found in whole blood from these patients, and the amount of bacterial 16S rDNA in blood increased after surgery. The blood microbiota was less diverse after surgery with significant relative enrichment of potential driver bacteria, such as Fusobacterium nucleatum . Blood microbiota and colorectal surgery